Depression among caregivers of children following traumatic brain injury in hospital universiti sains Malaysia. - Mohd Zin, Faridah (2012)
Depression among caregivers of children following traumatic brain injury in Hospital Universiti Sains Malaysia : Although it is generally accepted that traumatic brain injury leads to significant degree of depression among the caregivers, little is known about such impact on the population of North East Coast of Peninsular Malaysia. Hospital Universiti Sains Malaysia, being the only referral centre for traumatic brain injury in this region, it provides a suitable place to investigate the degree of depression and the possible risk factors. To determine the prevalence of depression and the associated factors among caregivers following traumatic brain injury in Hospital Sains Malaysia. This is a cross sectional study involving 208 caregivers of children following traumatic brain injury. They were recruited during follow up at the Neurosurgical Outpatient, Hospital Universiti Sains Malaysia from April 2010 until March 2011. Duration since injury ranged from 1 week to 75 months. The caregivers were requested to answer a set of guided questionnaires on socio demographic and a self administered Beck Depression Inventory as the instrument to screen for depression. Those who had scored more than 10 were considered depressed. The medical records of the TBI patients were reviewed for the injury factors. The prevalence of depression was 38.5% (95%CI: 31.89, 45.11). Depression among caregivers was significantly associated with income per capita (p=0.035). Depression among caregivers was not associated with severity of injury, outcome of injury, duration since injury or mode of injury. Socio demographic factors of the caregivers and the TBI patients, were also not associated with depression following traumatic brain injury, both by simple and multiple logistic regression. Prevalence of depression among caregivers of children following traumatic brain injury in Hospital Sains Malaysia was very much higher than the general population. Household income per capita was found to have significant association with depression. Other associated factors tested were found to have no association with depression among caregivers. Thus, depression has to be expected and assessed accordingly among the caregivers especially those with low household income per capita.